EVALUATION OF THE KNOWLEDGE OF TEACHERS ABOUT DENTAL TRAUMA IN A REGION OF SOUTHEASTERN ESPÍRITO SANTO IN BRAZIL - Jéssica Giovani; Maria Helena Monteiro de Barros Miotto (Sociedade Brasileira de Enfermagem em Feridas e Estética, 2024)
Introduction: Dental injuries are a public health problem and are described as the second largest demand for dental emergencies, with the school being one of the most frequent places. Objective: To measure the knowledge of teachers about the immediate conduct needed in the face of traumatic events. Materials and Methods: An observational, quantitative, cross-sectional study was carried out. Descriptive analysis was performed using frequency tables with number and percentage for sociodemographic variables, functional variables, and knowledge about dental trauma. The statistical package IBM SPSS 20 were used for analysis. Results: The teachers showed an deficient degree of information and ability to conduct first aid in such situations, which predisposes to a worrying scenario  that favors the sequelae and unfavorable prognoses, resulting in damage to the quality of life and early tooth loss. We found no statistically significant difference regarding location and time of work (rural or urban), level of education, age, and sex, since knowledge is absent in all scenarios. Conclusion: The worrying scenario of teacher unpreparedness to deal with traumatic dental situations justifies urgent need for health education actions and teacher training, as well as the inclusion of this theme in the curriculum of future professionals.